Role of Earth Sciences in Urbanization of Dera Ghazi Khan City, Punjab, Pakistan - Iqbal, Sheikh Muhammad; Khan, Muhammad Afaq; Khan, Azhar; Ahmed, Sarfraz (Journal of Himalayan Earth Sciences, 1997)
The role of the Earth Sciences in urbanization of big cities has become indispensable. The urbanization of Dera Ghazi Khan city has been executed through six maps of environmental Geology to conserve the environment of the area with application of earth sciences. The fast urbanization is due to rapid increase in population has caused severe stress on the environment which demands for more resources for water, mineral and aggregate material resulting in increase of dust, smoke, noise and health hazards in the area. The most striking problem of the area is acute shortage of drinking water in northern part and scientific devices are formulated to overcome this problem. This paper has five maps which will show: i) Quaternary geology, ii) Landform, iii) Resources of construction material, iv) Land-use planning and v) Water resources and its management. The data from these maps can be arranged in better way in which its applications would be helpful to urban designers, planners and financial agencies for speedy development of other cities of the Punjab as well as mega cities of the country with minimizing the environmental degradation.